INFLUENCE OF LONG-TERM DRAINAGE AND AGRICULTURAL USE OF THE TRUBIZH RIVER FLOOD ON THE AGRO-ECOLOGICAL CONDITION OF SOILS AND THE ENVIRONMENT - Бережняк, Евгений; Бережняк, Михаил; Карпенко, Максим (SWorldJournal, 2021)
The paper presents the results of research on the content of organic matter, ash, carbonates, sediments of peat soils of the Trubizh floodplain for a long period of drainage and their agroecological assessment according to R.S. Truskavetskiy. It is noted